Bunionette deformity corrected with "shortening" scarf osteotomy of the fifth metatarsal: mid-term results of a 34-cases - Necas, Libor; Hrubina, Maros; Skotak, Miroslav; Melisik, Marian; Lisy, Peter; Cibula, Zoltan (Foot and ankle surgery, 2020)
BACKGROUND: The aim of this study was to evaluate the clinical and radiological outcomes (in mid-term) after "shortening" scarf osteotomy of the fifth metatarsal for the treatment of bunionette deformity. METHODS: We retrospectively reviewed the functional score - American Orthopaedic Foot and Ankle Society (AOFAS) Lesser Toe Metatarsophalangeal-Interphalangeal Scale, radiographic results - 4th/5th intermetatarsal angle, varus angle of the 5th metatarsophalangeal joint and complications in a consecutive series of 34 feet (27 patients) with bunionette. Nine males and 18 females (mean age: 45 years) were included in the study. Three males and four females were operated bilaterally The patients were operated on between 2004 and 2015, and evaluated during 2017. RESULTS: The average AOFAS score improved from 59.4 to 93 at a mean follow-up of 7.2 years. The 4th/5th intermetatarsal angle and varus angle of the 5th metatarsophalangeal joint decreased from 13.9°/19.5° preoperatively to 6°/5.9° at final follow-up. No neurovascular damage was recorded. Complications arose in five feet (14.7%): delayed union (n=1), early infection (n=1), distal screw migration (n=1), asymptomatic non-union (n=1), transverse metatarsalgia (n=1). The osteotomy healed within less than three months except twoo (delayed union, non-union). Three feet needed additional surgery: screw removal (n=2), Weil osteotomy of 2nd-4th metatarsals (n=1). CONCLUSIONS: "Shortening" scarf osteotomy is an acceptable, but not complication-free, treatment option for the bunionette deformity and offers promising results in the mid-term.
Keywords: Female; radiografie; Radiography; výsledek terapie; ženské pohlaví; Osteotomy; lidé; Metatarsophalangeal Joint; Treatment Outcome; následné studie; Bunion, Tailor's; retrospektivní studie; osteotomie; Follow-Up Studies; Male; Aged; bunionette deformity; lidé středního věku; senioři; mužské pohlaví; Metatarsal Bones; Retrospective Studies; metatarzální kosti; Middle Aged; metatarzofalangeální kloub; Humans